Short-term retention of 99mTc activity in bone scintigraphy - Ali, W. M.; Sulieman, A.; Salah, H.; Almohammed, H.I.; Alkhorayef, M.; Bradley, D.A. * (Elsevier, 2021)
The objective of present study is estimation of the radioactivity held within the urinary bladder and kidneys 3 h post radiopharmaceutical (99mTc-MDP) administration, comparison being made via use of MIRDose. Using the conjugate-view method and built-in camera software Mediso XP Interview, urinary bladder and kidney radionuclide activities were calculated using patient clinical data acquired at the aforesaid 3 h post 99mTc-MDP injection juncture. The study was of a cohort of 40 patients attending for staging and cancer follow-up at the Nuclear Medicine Department, Royal Care International Hospital (RCIH), Sudan, Ethical and Research Committee approval for the study having been obtained. The radioisotope biokinetics were simulated using the Medical Internal Radiation Dose (MIRD) biokinetics model, specifically in regard to radionuclide activity in the kidneys and bladder. The results were compared with the data achieved via clinical study, showing the experimentally estimated radionuclide activity in the kidney to be greater by some 50% compared to that of simulation while the bladder radionuclide activity was found to be just 2% of the simulation result. The study also found that 0.9% of the administered radioactivity remained in the urinary bladder and kidneys 3 h post administration of the radionuclide, suggestive of low radiation dose to the urinary bladder and kidneys post 99mTc-MDP bone scans.